Renal tubular epithelial cells injury induced by mannitol and its potential mechanism. (15th October 2018) - Shi, Jinwan; Qian, Jiuzhan; Li, Hui; Luo, Hongjun; Luo, Wenhong; Lin, Zhexuan
Abstract: Administration of mannitol with high dose could induce extensive isometric renal proximal tubular vacuolization and acute renal failure in clinic. We previously demonstrated that mannitol-induced human kidney tubular epithelial cell (HK-2) injury. The objective of our present work was to further study the cytotoxicity of mannitol in HK-2 cells and its potential mechanism. Cell viability was assessed by an MTT method. Cell morphological changes were observed. Furthermore, levels of malondialdehyde (MDA) and glutathione (GSH) were measured. Flow cytometry was performed to determine cell apoptosis by using Annexin V-FITC and PI. In addition, the F-actin of cells was labeled by FITC-Phalloidin for observation of cytoskeleton. The MTT assay displayed that the cell viability decreased significantly in a dose- and time-dependent manner. The morphological changes were observed, including cell membrane rapture and cell detachment. The GSH concentration in HK-2 cells decreased dramatically in mannitol treatment group, while MDA content increased significantly. The results of flow cytometry indicated that apoptotic percentages of HK-2 cells increased in 250 mmol/L mannitol treatment group. After treatment with 250 mmol/L mannitol for 48 h, HK-2 cells showed disorganization of cytoskeleton and even exhibited a totally destroyed cytoskeleton. Therefore, high dose of mannitol has a toxic effect on renal tubular epithelial cells, which might be attributed to oxidative stress, destroyed cellular cytoskeleton and subsequent cell apoptosis.